SEX DIFFERENCES IN ADHD – DIAGNOSTIC AND THERAPEUTIC CHALLENGES - Marek, Aleksandra; Balińska, Wiktoria; Rogowska, Jagoda; Wąsik, Jakub (International Journal of Innovative Technologies in Social Science, 2026)
Attention-Deficit/Hyperactivity Disorder (ADHD) presents differently across sexes, yet current diagnostic and therapeutic frameworks remain largely based on male symptom profiles. This discrepancy contributes to the persistent underrecognition and misdiagnosis of ADHD in among girls and women. Females more commonly exhibit inattentive traits, emotional dysregulation, and internalizing symptoms, which are often misattributed to anxiety, depression, or personality disorders. As a result, many women receive a diagnosis only in adulthood, following years of impaired functioning, reduced self-esteem, and ineffective treatment for secondary symptoms. These delays carry significant psychosocial consequences, including higher risks of self-directed violence, relational difficulties, lower educational attainment, and unplanned pregnancy. Sex differences also extend to treatment. Evidence indicates that girls are less likely to receive stimulant medication in childhood and may respond differently to pharmacotherapy, with variable efficacy of methylphenidate and atomoxetine. Hormonal fluctuations across the menstrual cycle, pregnancy, and menopause further modulate symptom severity and treatment response, though research in this domain remains limited. Pregnancy presents unique challenges, as ADHD symptoms may intensify while medication options become more restricted due to safety considerations. These findings underscore the need for gender-sensitive approaches to ADHD diagnosis and management. Greater awareness of female-specific symptom patterns, masking behaviors, and hormonal influences is essential for improving early identification and optimizing therapeutic outcomes. Future research should prioritize sex-disaggregated data and explore hormonal and reproductive influences to inform more individualized treatment strategies for women with ADHD.